1989
DOI: 10.1176/ajp.146.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Mood disorders in the psychoneurologic borderland: three cases of responsiveness to carbamazepine

Abstract: Three patients with affective disorders with psychotic features were refractory to various combinations of psychotropic agents (antipsychotics, antidepressants, and lithium). Closer scrutiny revealed a seizure history in two patients and unusual neuropsychiatric features in the third patient. Subsequent substitution of carbamazepine for the antipsychotic resulted in control of the patients' psychoses. The authors describe clinical features that may identify the patient who may respond to carbamazepine. The mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Therefore, it may be suggested that carbamazepine responders may have an atypical bipolar disorder, characterized by mood-incongruent delusions and co-morbidity. Older studies had suggested a good response to carbamazepine in bipolar disorder patients with concomitant structural brain abnormalities and pathologies revealed by EEG recording [22]. It is not known whether the clinical features of responders to carbamazepine are similar to those with another mood-stabilizing anticonvulsant drug, valproate.…”
Section: Clinical Features Of Responders To Mood Stabilizersmentioning
confidence: 99%
“…Therefore, it may be suggested that carbamazepine responders may have an atypical bipolar disorder, characterized by mood-incongruent delusions and co-morbidity. Older studies had suggested a good response to carbamazepine in bipolar disorder patients with concomitant structural brain abnormalities and pathologies revealed by EEG recording [22]. It is not known whether the clinical features of responders to carbamazepine are similar to those with another mood-stabilizing anticonvulsant drug, valproate.…”
Section: Clinical Features Of Responders To Mood Stabilizersmentioning
confidence: 99%
“…Augmentation with lithium in four small, uncontrolled studies improved the response rate of psychotic depression, especially bipolar psychotic depression, to combination therapy [4]. In one report, open augmentation of antidepressant-antipsychotic combination therapy with carbamazepine was effective in 3 patients [105]. There has been more systematic interest in brief augmentation with mifepristone, an antagonist of the progesterone receptor and the glucocorticoid receptor type II, which has a low affinity for cortisol and helps terminate the stress response [19].…”
Section: Treatmentmentioning
confidence: 99%